Trends towards zero discharge of distillery effluents - Gokarn, A. N.; Pande, Anita R.; Mayadevi, S. (Trends towards zero discharge of distillery effluents, 2012)
In the present paper we have described briefly a customer friendly process for the treatment of distillery effluent to obtain colourless water.In order to bring about improvement of cost factor, our developmental efforts towards cheaper and efficient adsorbents have been elucidated. Further improvement of its cost factor could be achieved by enhancing the colour removal ability of the adsorbent (activecharcoal) with small quantities of oxidizing agents (in ppm level). Recent developments towards obtaining valueadded products from spent wash using various methodologies and techniques have been reviewed with a view to encourage technocrats and entrepreneurs to take lead in this challenging and economically attractive endeavor